Belgium priority as a partner for the Republic of Kazakhstan - Kasteyeva, Merey (Opción, 2019)
This article aims to examine the relationship of Kazakhstan with the European Union with regard to theoretical methodologies such as the analysis of literature and authors’ opinion, analyses of official juridical documents and statistics data. As a result, Partnership and Cooperation Agreements between Kazakhstan with the EU and Belgium as well has created the potential for the transition of bilateral cooperation to a qualitatively new level. Belgium is considered as one of diplomatic, trade-economic and investment partners’ priority because of its geographical position as a gate to Europe, and its central location closely connects it with the main European economies.